Gamification strategies and speaking fluency in EFL elementary students - Marin-Pacurucu, Byron Antonio; Argudo-Garzón, Antonio Lenin (IUSTITIA SOCIALIS, 2022)
Students in public schools from Ecuador have problems regarding speaking fluency due to the poor development of EFL teaching strategies and motivation issues. Students need constant teacher input, which provokes demotivation and low academic results. Gamification based on connectivism, constructivism, PPP methods, and communicative focus was used to solve and correct class deficiencies. In this context, this article has as objective to analyze the effect of gamification strategies in improving speaking fluency in EFL elementary school students from "Benjamin Sarmiento" School. The methodology used was based on mixed methods following an explanatory sequential design. A pretest and a posttest were created to measure starting points and development. The final result was the creation of a proposal integrating gamification tools into their learning that help them improve class motivation, their speaking fluency, and their acquisition of a new language.